Research on Performance of Covert Wireless Communication over Uplink LEO Satellite-Terrestrial Network - ZENG Shulei; CAO Bin (天地一体化信息网络)
The deployment of large-scale LEO satellite constellations is rapidly advancing, enabling seamless global coverage and supporting a wide range of applications.However, this proliferation of satellites also brings significant security concerns, including risk of eavesdropping and the detection of illegal communication activities.In response to these challenges, this paper investigates covert wireless communication over uplink satellite-terrestrial network. Specifically, by leveraging shot noise caused by ambient signals from terrestrial interferers, a terrestrial transmitter (Alice) can effectively obscure her signal from warden satellites. With the aid of stochastic geometry, the distributions of distances between the transmitter and satellites were analyzed, providing key insights into the uplink performance and interference experienced within a satellite's coverage area.Approximate expressions for the detection error probability and transmission outage probability were provided. Monte Carlo simulations validated the accuracy of the analytical methods used to assess covert communication performance.